(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
Review of Liz Atkins and Verity Duckworth, Research Methods for Social Justice and Equity in Education, Bloomsbury Research Methods for Education (London: Bloomsbury Academic, 2019). 336pp., 5 bw illus. 32.95. ISBN 9781350015463.